PERANCANGAN SISTEM ANTRIAN DAN JUMLAH KASIR DI SWALAYAN INDO JAYA DENGAN METODE SIMULASI - Harold - Hursepuny; Alvian - Sapulette (Admisi dan Bisnis, 2015)
In section cashier at the Indo Jaya supermarket there are five cashiers counterthat not all functioned. Cashier counter that functioned average was 2 counter. This was related to how many long queue. If supermarket is quiet first opened is 2 counter first, cashier counter advanced opened again depend on many at least long queue. To add and reduce cashier counter sometimes stated by the supervisor but more often to be carried out on its own (improvisation) by the officer cashier counter because they are the ones who know the condition how many cashier that have to be opened on a certain point in time. The working hours divided into 2 work shifts, the first shift started at 09.00 to 15.00 WIT, and second shift starts from 15.00 to 21.00 WIT. This research aims to find an alternative to the influence of cashier long queue and select number of cashier is right for every work shifts. By using analysis of queue theory with the approach Simulation models using samples as many as 200 customers who come, obtained the following result: From data processing result by distribution pattern that would be a good time to time service is normal distribution and price 87.04 seconds and standard deviation of 42.76. While for the service distribution testwould be a good is Weibull with average 94.92 seconds and standard deviation of 64.32